Dos tempos de escola aso dias atuais reminiscências duradousras da experiência escolar - Vieira, Marcílio de Souza (2008)
This study it treats on the marks of the school experience in the individuation process of the subject and has as general aim to know of that it forms these experiences, the spite of the curricular and pedagogical questions, influences this process. It searched to interpret the experiences strengthened during the school education and the trajectories of confrontation of the diverse situations lived in the school. It was tried,also,to understand the direction of the critical school events and equally as the familiar way can influence in the choices and formation of the citizens through the pedagogical investment. Furthermore, it was reflected on the reasons that had taken some to remain in the school environment are as student or, later, of the side of there ,as teacher. For in such a way, it realized a qualitative research with a phenomenological inspiration using narratives interviews carried with four subjects, from which if it identified the main characteristics, structure, conditions of origin, the social context, the school strategies, the forms as they had been managed and its consequences. The analysis of the stories clearly left two basic axles about the school experience that if detach in the constitution of the subjects: in a hand, the dynamics of the lived school environment left undeleted marks in the memory that had been determinative for the personal choices; on the other hand,the familiar reference, through its different forms of pedagogical investment,had a decisive influence. The agreed marks of the school and the family had left an important legacy for formation of the subjects and the choices that had made during their lives, especially in the aiming of its professional careers. Invariably, it was perceived in the inquiry, that much of the pupil who if was persists in the adult and professional of today. Thus, the school I it s part of professional I that it exists in each one. The citizen, the person and the professional are derived from the processes of socialization and individuation, which to a large extent are defined during the school life. And it s with the use of this school capital , acquired in the school times, that we have conditions to develop the many social roles in the current days